2021
DOI: 10.1111/jocn.15890
|View full text |Cite
|
Sign up to set email alerts
|

Developing a theory to help guide End‐Stage Renal Disease Patients to adapt to Peritoneal Dialysis: A grounded theory study

Abstract: Aim and objectives:The aim of this study was to develop a theory to help guide patients with end-stage renal disease to adapt to peritoneal dialysis.Background: Taiwan ranks first worldwide in end-stage renal disease incidence and dialysis prevalence. Many patients cannot accept long-term dialysis treatment and thus face several physical and psychological suffering. No theory has yet been developed to help guide patients with end-stage renal disease to adapt to peritoneal dialysis.Design: A grounded theory app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…18,33 Consistent with the biopsychosocial model for relating patient life-experience to health outcomes, 34,35 patient behavioural responses to physical, emotional, interpersonal and environmental challenges were crucial for success. Frameworks related to PD adaptation theory, 36 motivation, 37 learning theories such as a growth mindset 38,39 and emotional intelligence, or the ability to understand and problem solve with emotional information, 40 could support behavioural interventions to reduce PD drop-out.…”
Section: Discussionmentioning
confidence: 99%
“…18,33 Consistent with the biopsychosocial model for relating patient life-experience to health outcomes, 34,35 patient behavioural responses to physical, emotional, interpersonal and environmental challenges were crucial for success. Frameworks related to PD adaptation theory, 36 motivation, 37 learning theories such as a growth mindset 38,39 and emotional intelligence, or the ability to understand and problem solve with emotional information, 40 could support behavioural interventions to reduce PD drop-out.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation is one of the strategies that enables them to live with the disease and not just live for the disease [ 30 ]. People with CKD employ strategies to adapt to peritoneal dialysis, such as positive self-regulation, adjustments to reduce the impact of treatment on their lives, and changes in the dialysis method [ 17 ]. One study found that for people with CKD, adapting their routines to dialysis treatment allowed them to maintain their family relationships [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having to visit the hospital three times a week for hemodialysis; having to change peritoneal fluid daily; being subject to significant dietary, social and leisure restrictions and the loss of independence significantly reduce people’s quality of life [ 15 , 16 ]. Therefore, when choosing a therapy, one of the main considerations of people in the final stages of CKD is maintaining the highest possible quality of life [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation